SIMILARITIES AND DIFFERENCES IN THE SEMANTIC STRUCTURE OF ENVIRONMENTAL TERMS - Nigmatullina, Almira Shamsunovna (Журнал иностранных языков и лингвистики, 2023)
This article reveals general and specific manifestations of the semantic ambiguity of terms in languages. Scientific novelty lies in a new approach to describing the multilingual terminology of ecology.